2020
DOI: 10.3390/catal10040368
|View full text |Cite
|
Sign up to set email alerts
|

Purifying of Waste Tire Pyrolysis Oil Using an S-ZrO2/SBA-15-H2O2 Catalytic Oxidation Method

Abstract: Heavy fuel oils contain a high amount of sulfur. In this work, an extent amount of sulfur content waste tire pyrolysis oil (WTPO) was used as a fuel feedstock. A promising alternative oxidative desulfurization (ODS) method was applied in sulfur removal from WTPO using a S-ZrO2/SBA-15 solid acid catalyst, hydrogen peroxide (H2O2) as an oxidant and acetonitrile as an extracting solvent at varied conditions. The prepared catalyst was characterized by X-ray diffraction (XRD), Bruanuer-Emmet-Teller (BET) method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Additionally, the original high sulphur content represented an obstacle to an efficient removal by using a biphasic approach with the extracted sulphone that rapidly reached the saturation of watery phase. Nonetheless, CC and TC displayed catalytic performances very close to systems operating on tires derived oil [28,60] even if none of previously published research based on biphasic systems treated oil with a sulphur content high such the one used in the present study.…”
Section: Catalytic Activity Of CC and Tc In Oxidative Desulphurization Of Oil Recovered From Pyrolysis Of Waste Tiresmentioning
confidence: 51%
“…Additionally, the original high sulphur content represented an obstacle to an efficient removal by using a biphasic approach with the extracted sulphone that rapidly reached the saturation of watery phase. Nonetheless, CC and TC displayed catalytic performances very close to systems operating on tires derived oil [28,60] even if none of previously published research based on biphasic systems treated oil with a sulphur content high such the one used in the present study.…”
Section: Catalytic Activity Of CC and Tc In Oxidative Desulphurization Of Oil Recovered From Pyrolysis Of Waste Tiresmentioning
confidence: 51%
“… 29 , 30 Despite all this, other methods of ex situ desulfurization were unable to achieve the same efficiency as HDS, although some disadvantages of HDS could be eliminated. 31 , 32 …”
Section: Introductionmentioning
confidence: 99%
“…Hydrodesulfurization (HDS) was a traditional method of ex situ desulfurization, and the most commonly used to fulfill the sulfur removal of oil products. The experimental results of HDS under different catalysts and parameters demonstrated that the maximum removal efficiency could reach 99.9%. , Different from sulfides without ring structure, dibenzothiophene (DBT) and substituted DBTs were more difficult to be removed through HDS owing to the influence of steric resistance. , Despite all this, other methods of ex situ desulfurization were unable to achieve the same efficiency as HDS, although some disadvantages of HDS could be eliminated. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that WTPO has a higher sulfur content (0.7-1.7) than the standard liquid fuel. This high sulfur content limits the application of WTPO in real combustion engines (Table 1) [5,[11][12][13] because the presence of sulfur compounds (Figure 1) in WTPO causes the emission of highly toxic SOx, which is a considerable environmental and health threat, during its combustion. Thus, an efficient desulfurization method to remove sulfur compounds from WTPO prior to using it alone or in commercial diesel fuels is urgently needed.…”
Section: Introductionmentioning
confidence: 99%